Spanish agriculture and water: Educational implications of water culture and consumption from the Farmers’ Perspective - Tójar-Hurtado, Juan Carlos; Mena-Rodríguez, Esther; Fernández-Jiménez, Miguel Ángel (MDPI, 2017)
The responsible management and consumption of water is a challenge that involves all segments of society. Having access to sufficient quality and quantity of water is not only a technological issue, but requires that the adopted measures and programmes take into account the dimensions of society and education. Spanish agriculture, as in other areas of the world, is a major consumer of water and more so than other sectors, including household consumption. Within the field of environmental education, this study covered the water culture and consumption of Andalusian farmers, based on their own perceptions. For this purpose, a questionnaire was created and validated, and included a sample of 1030 farmers selected with pseudorandom number sampling. An analysis of the data showed relevant results with respect to the values and notions supporting the justification for farmer behaviours, both from a cognitive-representative viewpoint and from an affective-expressive stance, as well as assertions made by the irrigators about other key sectors concerning the responsible management of water usage and water consumption. The findings of this study may assist in the design of environmental education programmes addressing this sector, which could also include other similar populations.
Keywords: Educacion ambiental; Foreign countries; Agricultural occupations; Environmental education; Surveys; Sustainability